Ideology in language use : pragmatic guidelines for empirical research - Verschueren, Jef. (Cambridge : Cambridge University Press, 2012)
'The relationship between language and ideology has long been central to research in discourse analysis, pragmatics, sociolinguistics and linguistic anthropology, and has also informed other fields such as sociology and literary criticism. This book, by one of the world's leading pragmatists, introduces a new framework for the study of ideology in written language, using the tools, methods and theories of pragmatics and discourse analysis. Illustrations are drawn systematically from a coherent corpus of excerpts from late nineteenth- and early twentieth-century history textbooks dealing with episodes of colonial history and in particular the 1857'Indian Mutiny'. It includes the complete corpus of excerpts, allowing researchers and students to evaluate all illustrations; at the same time, it provides useful practice and training materials. The book is intended as a teaching tool in language-, discourse- and communication-oriented programs, but also for historians and social and political scientists'--
Machine generated contents note: Introduction; Part I. Language Use and Ideology; Part II. Pragmatic Rules of Engagement; Part III. Pragmatic Guidelines and Procedures; Conclusion.
Includes bibliographical references (p. 357-371) and index.
Keywords: Language and culture; Ideology; Discourse analysis -- Social aspects; Pragmatics